Recyclable, but not recycled—an indicator to quantify the environmental impacts of plastic waste disposal - Venkatachalam, Venkateshwaran; Spierling, Sebastian; Endres, Hans-Josef (Frontiers in Environmental Science, 2024)
With an exponential increase in the production and consumption of plastic products over the last few years, the predominantly linear (take-make-dispose) economy of the plastic life cycle has captured global attention. Even though plastic products offer versatile benefits with their properties across different sectors, with a global recycling rate of less than 10%, it is challenging to reduce the pollution generated by plastic waste. Also, the loss of resources due to the uncontrolled disposal of plastic waste has been projected to cause long-term negative effects on the environment. To ensure a better circularity of the plastic flows across the world, it is essential to design plastic products that have an adequate infrastructure to recover and recycle the waste no matter where they are used. The polymer manufacturers and the plastics converters must account for the environmental impacts of the resources lost in the environment due to the lack of recycling infrastructure as a part of Extended Producer Responsibility. This study introduces an indicator that accounts for the loss of resources and proposes for a better methodology to quantify the environmental impacts of polymers and plastic products, based on their recyclability and the availability of recycling infrastructure to handle them. By integrating the loss of resources with the environmental impacts of specific polymers used in specific plastic products, the stakeholders across the value chain have the choice to select the polymers and products that are actually recycled, thereby reducing their environmental impacts and increasing the circularity.